2017
DOI: 10.1515/reveh-2016-0029
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of ETS exposure in a sample of Slovak pregnant women

Abstract: Abstract Environmental tobacco smoke (ETS) is one of the greatest and the most frequent environmental toxic exposures presenting a high risk to children and to their mothers as well. The aim of the study was to find determinants of the household ETS in the sample of pregnant women living in the household with smokers and to assess their physical and mental health. The survey was distributed to women being seen for follow-up at the obstetric/gynecology departments in hospitals a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 10 publications
2
16
0
Order By: Relevance
“…The results of our previous studies show that ETS is one of the most important health hazards influencing the physical and mental health of the exposed non-smoking partners [20]. The study published by the members of our research team on a nationally representative data from the year 2000 to 2004 Medical Expenditure Panel Survey in the USA [18] showed a relationship between living with smokers and worsened maternal physical and mental health in non-smoking mothers with children.…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…The results of our previous studies show that ETS is one of the most important health hazards influencing the physical and mental health of the exposed non-smoking partners [20]. The study published by the members of our research team on a nationally representative data from the year 2000 to 2004 Medical Expenditure Panel Survey in the USA [18] showed a relationship between living with smokers and worsened maternal physical and mental health in non-smoking mothers with children.…”
Section: Discussionmentioning
confidence: 86%
“…Researchers from the Comenius University's Obstetrics and Gynecology (OB/Gyn) Department and Institute of Hygiene in Bratislava, Slovakia distributed surveys to pregnant women in the 36th − 41st week of pregnancy being seen for the follow-up at the OB/Gyn Department of the Faculty Hospital and Clinic. This survey is the continuation and re-analysis of the previous survey that was designed to evaluate environmental, behavioral, and psychosocial factors in the lives of women [20]. The results of the study have shown that ETC exposure is an independent risk factor associated with the worse physical health of non-smoking mothers in the reproductive age and the worse mental health in the smaller sample of pregnant women [20].…”
Section: Methodsmentioning
confidence: 97%
See 3 more Smart Citations